The marginal value of an accession - Zohrabian, Armineh; Traxler, Gregory; Caudill, Steven; Smale, Melinda (International Food Policy Research Institute, 2003)
Ascribing productivity gains to specific genes or accessions is difficult because of the nature of the research process in genetic enhancement, the relationship among genes within a genome, and the interaction of genes with the environment of the crop. Even in commercialized agriculture, the value of unimproved material used for genetic enhancement cannot be measured directly because only finished (or nearly finished) crop varieties are traded in markets (Brief 7). What is the expected benefit from using an additional, unimproved genebank accession in crop breeding?